Spacer Engineering of Diammonium‐Based 2D Perovskites toward Efficient and Stable 2D/3D Heterostructure Perovskite Solar Cells (Adv. Energy Mater. 2/2022). Issue 2 (13th January 2022) - Niu, Tianqi; Xie, Yue‐Min; Xue, Qifan; Xun, Sangni; Yao, Qin; Zhen, Fuchao; Yan, Wenbo; Li, Hong; Brédas, Jean‐Luc; Yip, Hin‐Lap; Cao, Yong
Abstract : 2D/3D Perovskites In article number 2102973, Qifan Xue, Hong Li, Jean‐Luc Brédas, Hin‐Lap Yip and co‐workers report a spacer tailoring strategy to regulate the interfacial properties of diammonium‐based 2D/3D perovskite heterostructures, which allows the well‐controlled phase composition and crystalline orientation and enhanced surface passivation of a 2D capping layer. This work provides an important insight into the further development of high‐performance perovskite solar cells through interfacial reconstruction.